2019
DOI: 10.3390/ijms21010070
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Blood Level of MFSD2a as a Potential Biomarker of Alzheimer’s Disease

Abstract: The protein Major Facilitator Superfamily Domain containing 2A (MFSD2a) was recently described as the primary carrier for docosahexaenoic acid (DHA) into the brain. Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by lower DHA levels in blood lipids. The aim of this study was to investigate the expression of MFSD2a in the whole blood and brain as a potential biomarker of AD. Three groups were established: 38 healthy controls, 48 subjects with moderate AD (GDS4), and 47 with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…More of the available evidence indicates the role of n6 to n3 PUFA ratio in the cognitive dysfunctions [ 44 , 45 ]. Other studies did not report any differences of this FA in AD patients compared to controls [ 43 ]. Observations presented by other authors differ from our results, but it should be emphasised that we investigated a specific group of stroke survivors and similar analyses have not been presented yet.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…More of the available evidence indicates the role of n6 to n3 PUFA ratio in the cognitive dysfunctions [ 44 , 45 ]. Other studies did not report any differences of this FA in AD patients compared to controls [ 43 ]. Observations presented by other authors differ from our results, but it should be emphasised that we investigated a specific group of stroke survivors and similar analyses have not been presented yet.…”
Section: Discussionmentioning
confidence: 86%
“…This FFA was found to be negatively associated with backwards repeating in Digit Span Test, which suggests its ambiguous role in predicting the working memory. In a limited number of studies available, no differences were identified in serum vaccinic acid level between AD patients and controls [ 43 ]. There are no available data regarding vaccinic acid and cognitive outcome in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between the primary fatty acid amide level in plasma and Aβ pathology, hippocampal volume, and cognitive score was also reported [ 310 ]. Instead, opposite trends were observed regarding the serum content of two saturated fatty acids (palmitic and myristic acids) and three unsaturated fatty acids (oleic, linolenic, and docosahexaenoic acids), with docosahexaenoic acid being the most significantly decreased in AD compared to controls [ 311 , 312 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter has also been associated with neuronal loss in Alzheimer's disease. The reduction of other proteins, including Src homology region 2 domain-containing phosphatase- 1 (SHIP1) [35] , [36] , BTB Domain And CNC Homolog 1 ( BACH1) [37] , [38] , BCL6 Transcription Repressor (BCL6) [39] , BCL10 Immune Signaling Adaptor (BCL10) [40] , [41] , and Major Facilitator Superfamily Domain Containing 2A (MFSD2A) [42] , [43] , have each been linked to progressive Alzheimer's disease. It has been shown in in vivo mouse models of COVID-19 that high circulating levels of spike protein can modulate some of these proteins in the brain and we have previously reported altered expression of NMDAR2, nNOS, SHIP1, and MFSD2A in the brains of people who died of COVID-19 who did not have a history of pre-existing dementia [11] .…”
Section: Introductionmentioning
confidence: 99%